Relation between Systemic Inflammatory Index (SII) and Hair Trace Elements, Metals and Metalloids Concentration in Epicardial Coronary Artery Disease—Preliminary Report - Tomasz Urbanowicz; Anetta Hanć; Anna Olasińska-Wiśniewska; Anna Komosa; Krzysztof J. Filipiak; Artur Radziemski; Mateusz Matejuk; Paweł Uruski; Andrzej Tykarski; Marek Jemielity (Reviews in Cardiovascular Medicine, 2023)
Background: Coronary artery atherosclerosis development and progression are related to generic, clinical, and lifestyle factors combined with inflammatory activation. The relationship between trace element concentration and morbidity is under investigation to gain a clearer understanding of underlying pathological processes. Methods: Thirty-five consecutive patients (22 males and 13 females) with a median [interquartile range (IQR)] age of 67 (61–73) years presenting with anginal symptoms were included in the single center prospective analysis in 2022 and divided into a epicardial coronary artery disease (CAD) and non-CAD group. Scalp hair chemical analysis and inflammatory markers from a peripheral blood count were analyzed. Results: The correlation analysis of elements and inflammatory indexes showed statistical significance between median hair lithium (Li) concentration and the systemic inflammatory index (SII) (r = –0.476, p = 0.046), antimony (Sb) (r = –0.521, p = 0.028) followed by chromium (Cr) (r = –0.478, p = 0.045) and iron (Fe) (r = –0.604, p = 0.008) in the CAD group. Similar correlations were not found in non-CAD group. Conclusions: The correlation between scalp hair lithium (Li), antimony (Sb), chromium (Cr) and iron (Fe) concentration and the systemic inflammatory index (SII) were revealed only in patients with coronary artery disease. Our analysis identified a strong correlation between inflammatory activation and iron concentration.